ANALISIS FILOGENETIK DENGUE DI INDONESIA - Aryati Aryati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Molecular epidemiology is needed to solve the problem for endemic Dengue Hemorrhagic Fever in Indonesia.This research has been carried out consisting of 525 Dengue Hemorrhagic Fever sera, according to the WHO criteria.These sera were collected from 19 cities in Indonesia comprising the islands of Sumatera, Batam, Kalimantan, Sulawesi, Papua, Java,Bali and Lombok from 2003 until 2005. The immune response profile was as follows 57.14% (300/525) secondary infection, 12.57%(66/525) primary infection, 4.20% (22/525) equivocal and 26.09% (137/525) negative. From 192 PCR samples, 100 (52%) serawere positive, consisting of 65% DEN-2, 15% DEN-3, 12% DEN-4 and 8% DEN-1. Homology analysis showed nucleotide differences incapsid region DEN-2 serotypes, while DEN-3 serotypes were relatively consistent. Phylogenetic analysis using envelope (E) gene revealedthat the Cosmopolitan genotype from Gorontalo in 2005, is currently circulating locally, with the potential to cause a severe hemorrhagicdisease. Members of this genotype were closely related to viruses from Malaysia, Singapore, Thailand, Philippines and Australia. Theisolate from Jakarta, 2003 showed DEN-3 with I genotype. This genotype was similar to the isolate from Indonesia 1978, 1985, andalso from Thailand 1992, Philippines 1997, and Fiji 1992. These results showed Cosmopolitan genotype from DEN-2 was similar toSoutheast Asia countries. It was also revealed that genotype-I from DEN-3 showed no change over the years since 1978.